Prevalence, Pattern and Sociodemographic Correlates of Psychosocial Disorders in Obese Adolescents in Enugu, Nigeria - Okechukwu N Ozoalor; Anthony N Ikefuna; Ann E Aronu; Ngozi C Ojinnaka (International Journal of Medicine and Health Development, 2022)
Background: Adolescent obesity is a serious public health issue. Inconsistent findings on its association with mental health problems are reported. Objective: This study aimed to determine the prevalence, pattern, and sociodemographic correlates of psychosocial disorders among obese adolescents in Enugu metropolis, Nigeria. Materials and Methods: A cross-sectional study was conducted over a 5-month period in 16 secondary schools in Enugu, Nigeria. A multi-staged systematic sampling technique was used to select participating schools. A total of 4364 adolescents aged 10–19 years from these schools were screened for obesity by measuring their height and weight, and calculating their body mass indices (BMIs), which were plotted on the Centers for Disease Control and Prevention BMI percentile chart. Seventy-four obese students were identified, and from their respective class registers, systematic sampling scheme was applied in selection of equal number of apparently healthy normal BMI (5th–84th percentile) controls matched for age and sex. The youth version of the Pediatric Symptom Checklist was used to screen for psychosocial disorder in the study participants. Results: The prevalence of psychosocial disorder was 17.6% and 12.2% among the obese and control adolescents, respectively (P = 0.02). Attention and externalizing problems were the highest among the obese adolescents, whereas psychosocial disorders were more in females than males (28.1% vs 9.5%; χ2 = 4.34, P = 0.04). Conclusion: Obese adolescents have a higher prevalence of psychosocial disorder compared to controls, with attention and externalizing problems being most common, and this was influenced by gender. Periodic assessment of the mental health of obese adolescents is advocated.